Thermal degradation assessment, impact strength, and hardness of combination epoxy and polystyrene powder composite - Jubier N.J.; Al-Jorani K.R.; Ali A.A. (Kuwait Journal of Science)
The present study investigates the reactions of polystyrene and epoxy/polystyrene powder composites, exploring different weight percentages (8%, 12%, and 16%) of polystyrene during decomposition under highly elevated temperatures within a nitrogen atmosphere. The findings reveal that polystyrene content significantly influences the thermal behavior of pure epoxy, with a higher polystyrene content correlating with the increased thermal stability of the composites. This study observed a three-stage mass loss process by examining the reaction kinetics of thermal decomposition using the Coats-Redfern approach. Initially, weight reduction occurs due to moisture and volatile elimination, followed by a smooth mass loss phase attributed to weaker polymer chain linkages and, ultimately, char formation. Chemical kinetic parameters, such as activation energy and frequency factor, were successfully determined using the Coats-Redfern approach, with a first-order reaction observed across all data points, demonstrating a high R-square mean value of 99.8%. Differential scanning calorimetry (DSC) and thermal gravitational analysis (TGA) analyses revealed an increase in glass temperature from 86.95 to 92.85 °C and an elevation in activation energy from 75.38 to 92.85 kJ/mol with increasing polystyrene content (0–16 wt%). Furthermore, the study investigated the influence of thermodynamic parameters. In terms of mechanical properties, increasing polystyrene content reduced impact strength (from 8.5 to 4.23 Kj/m2). In contrast, hardness increased from 77.5 for pure epoxy to 80.4 at 12 wt% polystyrene content in the composite. These findings underscore the importance of thermal stability results in developing a comprehensive understanding of thermal decomposition processes, informing future research endeavors and industrial applications. © 2024 The Authors